A review on financial and non-financial measures of supply chain performance - Baraka Israel; Leticia Mahuwi; Beny Mwenda (International Journal of Production Management and Engineering)
This study ascertains the pertinent measures and metrics of supply chain performance through an extensive literature review. A total of 53 international peer-reviewed journal articles published between 2012-2021 were retrieved from Scopus, Emerald insight, Elsevier and Springer databases for review. The articles reviewed were selected and categorised based on the approach, scope and contribution in assessing and ascertaining the measures and metrics of supply chain performance. Limited to the review of literature, this study provides a benchmark and approaches for ascertaining the level of supply chain performance from financial and nonfinancial perspectives. Throughout the review, the study found inventory turnover ratio, supply chain and logistics costs and cash flows reflected in terms of ROI, ROE, ROA, profit margin, working capital and assets as the prime financial measures of supply chain performance. Moreover, the study found customer satisfaction, delivery performance, quality services, enhanced relationships and competitive advantages as the key non-financial measures of supply chain performance. The study concludes and recommends the financial and non-financial measures as the appropriate approaches for ascertaining the level of supply chain performance. In order to appropriately ascertain the level of supply chain performance, performance measurement should be accounted for by all actors at each node of the supply chain, using the same approach, measures and metrics. Additionally, further studies are required to address the benefits and issues that impede supply chain performance and measurements across different sectors of the economy.